Presentation: Around social actors - Valle Rondón, Fernando (2010)
We wanted to dedicate this issue to some social actors who were the protagonists of two decisive moments in Peruvian history: the culminating expansive period of the Inca Empire and the stage of exploration, demarcation and territorial settlement of the conquering expeditions. Recent historiography has been largely enriched by research on various agents involved in both deeply connected historical processes. The purpose of this issue of Allpanchis is to broaden the discussion around the protagonists of Andean history, whose trajectories can and should be studied in detail from various perspectives.